A cultura organizacional de uma instituição pública de saúde: ferramenta para a compreensão de fenômenos organizacionais complexos - Jordão, Rodrigo Aquino (2014)
The implementation of the Brazilian National Health System has brought several challenges to the management of health. Due to the decentralization of services, the role and the relationship between the three federative agents have dramatically changed. Seeking for alternatives to better cope with this setting, the cultural studies are thought to be relevant in aiding the understanding of the complex organisational phenomena. This study aimed to analyse the organisational culture’s elements of a public health institution according to Hofstede and Schein. It is an exploratory case study employing a qualitative methodology. Data triangulation was performed, using in-depth interview, focus group, documental analysis and unsystematic observation. Data treatment involved content analysis. The results suggest that practical elements of the institution’s culture (symbols, heroes and rituals) converge on the following values: the technicism, the assistance, and the hierarchy. It was concluded that such a cultural system exalts the professional qualification, is focused on work processes, and suffers from the consequences of health underfunding. These implications may act as barriers to the institution’s performance, such as the difficulty in communication and interlocution, apolitical behaviour, negligence in results seeking, and the uncritical and isomorphic reproduction of national policies. It is suggested the drawing of management strategies supported in organisational theories that may equalize the actual values and cultural practices of the institution.